ANALISIS TINGKAT BAHAYA EROSI (TBE) DI DAS DUA LAUT KABUPATEN TANAH BUMBU - Eka Hardiana; Syarifuddin Kadir; Yusanto Nugroho (Universitas Lambung Mangkurat, 2020)
Erosion is the process of eroding the surface layer of soil due to surface flow. Erosion degrades soil quality as a medium grows on vegetation. This study aims to analyze the magnitude of the erosion rate and identify the level of erosion hazard in the DAS Dua Laut. Research method using USLE (Universal Soil Loss Equation) method with observation point using purposive sampling taking into account the land slope class.The results showed that from all units of DAS Dua Laut, the highest erosion value was found on slope> 25-40% with scrubland cover that was 231,78 ton /ha/year, while on slope> 8-15% with vegetation rubber obtained the lowest value of 10.53 tons /ha/year.This shows that land conversion gives influence to the rate of erosion especially on steep slopes. The erosion hazard level of all land units and land cover shows variations in land class in the form of very light classes (0-SR), light (1-R), medium (II S and III S), weight (III B) and very heavy (IV- SB).Keywords; soil erosion, DAS Dua Laut, Erosion Hazard Level